2021
DOI: 10.20944/preprints202104.0443.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Elucidating the antimycobacterial mechanism of action of ciprofloxacin using metabolomics

Abstract: In the interest of developing more effective and safer anti-Tuberculosis treatment, we aimed for a better understanding of the antimycobacterial action of ciprofloxacin against Mycobacterium tuberculosis (Mtb). We used GCxGC-TOF-MS and well described metabolomics statistical approaches, to investigate and compare the metabolic profiles of Mtb in the presence and absence of the drug. The metabolites that best describe the differences between the compared groups were identified as markers characterizing the chan… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 132 publications
(162 reference statements)
0
1
0
Order By: Relevance
“…It has also been demonstrated that ciprofloxacin, in addition to its effect on DNA gyrase, can cause reduction in the amount of DNA, RNA, and protein, as well as phospholipids, galactose, arabinose, glucosamine, and the mycolic acid of the M. smegmatis cell wall. However, these findings should be confirmed in the further studies ( Figure 2 ) ( 11 ). Ciprofloxacin affects several Gram-positive bacteria such as Staphylococcus, Streptococcus, Enterococcus, Bacillus spp., and Mycobacterium .…”
Section: Ciprofloxacin Characteristicsmentioning
confidence: 66%
“…It has also been demonstrated that ciprofloxacin, in addition to its effect on DNA gyrase, can cause reduction in the amount of DNA, RNA, and protein, as well as phospholipids, galactose, arabinose, glucosamine, and the mycolic acid of the M. smegmatis cell wall. However, these findings should be confirmed in the further studies ( Figure 2 ) ( 11 ). Ciprofloxacin affects several Gram-positive bacteria such as Staphylococcus, Streptococcus, Enterococcus, Bacillus spp., and Mycobacterium .…”
Section: Ciprofloxacin Characteristicsmentioning
confidence: 66%